The Importance of Internal and External Factors for the Selection Decision of Expatriates - Sugavaneswaran, Ramachandran; Šarkiūnaitė, Ingrida (Vilnius University Open Series, 2021)
Today’s global business environment sets the platform for international employee assignments. As organisation globalise their operations, the roles and responsibilities of the Human Resource department are transformed and face the pressure of globalisation. Therefore, the selection of expatriates to fill international assignment is challenging because of the complex nature of internal and external factors of the selection decision of expatriates like Cost, Expatriate Performance, Expatriate Failure, Political factor, Legal factor, Economic factor, Socio-culture, Family requirements, and Multinational enterprise requirements (MNE), etc. The result of the studies shows the complex nature of the expatriate selection decision during the international assignment which will have a huge impact on the selection decision of expatriates and the success of the organisation on the global level market in the world of competition.